Results of a prospective multicentre myeloablative double‐unit cord blood transplantation trial in adult patients with acute leukaemia and myelodysplasia. (1st October 2014) - Barker, Juliet N.; Fei, Mingwei; Karanes, Chatchada; Horwitz, Mitchell; Devine, Steven; Kindwall‐Keller, Tamila L.; Holter, Jennifer; Adams, Alexia; Logan, Brent; Navarro, Willis H.; Riches, Marcie; the RCI BMT 05‐DCB Protocol Team
Summary Double‐unit cord blood (CB) grafts may improve engraftment and relapse risk in adults with haematological malignancies. We performed a prospective high‐dose myeloablative double‐unit CB transplantation (CBT) trial in adults with high‐risk acute leukaemia or myelodysplasia (MDS) between 2007 and 2011. The primary aim was to establish the 1‐year overall survival in a multi‐centre setting. Fifty‐six patients (31 acute myeloid leukaemia, 19 acute lymphoblastic leukaemia, 4 other acute leukaemias, 2 myelodysplastic syndrome [MDS]) were transplanted at 10 centres. The median infused total nucleated cell doses were 2·62 (larger unit) and 2·02 (smaller unit) x 107/kg. The cumulative incidence of day 100 neutrophil engraftment was 89% (95% confidence interval [CI]: 80–96). Day 180 grade II‐IV acute graft‐versus‐host disease (GVHD) incidence was 64% (95%CI: 51–76) and 36% (95%CI: 24–49) of patients had chronic GVHD by 3‐years. At 3‐years post‐transplant, the transplant‐related mortality (TRM) was 39% (95%CI: 26–52), and the 3‐year relapse incidence was 11% (95%CI: 4–21). With a median 37‐month (range 23–71) follow‐up of survivors, the 3‐year disease‐free survival was 50% (95%CI: 37–63). Double‐unit CBT is a viable alternative therapy for high‐risk acute leukaemia/ MDS in patients lacking a matched unrelated donor. This is especially important for minority patients. The relapse incidence was low but strategies to ameliorate TRM are needed.